Redescription of Hymenopenaeus obliquirostris (Crustacea, Decapoda, Penaeoidea, Solenoceridae) and descriptions of two new species of Hymenopenaeus from the Indo-West Pacific - Crosnier, Alain; Dall, William (Zootaxa, 2004)
Hymenopenaeus obliquirostris (Bate, 1881), a relatively poorly known species, is redescribed, figured and compared with H. halli Bruce, 1966. Two other species of Hymenopenaeus, H. methalli from the southwest Pacific and H. fallax from Hawaii, are described as new. All these species are closely related to one another. They are distinguished essentially by the presence or absence of a postrostral carina, the presence or absence of a fixed spine on the merus of the first pereopods, and the shape of parts of the thelycum and petasma.